2015
DOI: 10.1186/s12889-016-2772-z
|View full text |Cite
|
Sign up to set email alerts
|

Are pit latrines in urban areas of Sub-Saharan Africa performing? A review of usage, filling, insects and odour nuisances

Abstract: BackgroundA pit latrine is the most basic form of improved sanitation which is currently used by a number of people around the globe. In spite of the wide spread use, known successes and advantages associated with pit latrines, they have received little attention in form of research and development. This review focuses on the usage and performance (filling, smell and insect nuisance) of pit latrines in urban areas of sub-Saharan Africa (SSA) and proposes approaches for their improvements and sustainability.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 52 publications
5
91
0
Order By: Relevance
“…In the informal settlements of most developing countries, sanitation facilities are often shared among a number of households, and the most dominant sanitation technology is the pit latrine (traditional pit latrine, simple pit latrine or ventilated improved pit latrine) (Nakagiri et al 2016). Sanitation decisions that need to be made in such a context include investment in, repair, emptying and maintenance (cleaning) of these latrines.…”
Section: Discussionmentioning
confidence: 99%
“…In the informal settlements of most developing countries, sanitation facilities are often shared among a number of households, and the most dominant sanitation technology is the pit latrine (traditional pit latrine, simple pit latrine or ventilated improved pit latrine) (Nakagiri et al 2016). Sanitation decisions that need to be made in such a context include investment in, repair, emptying and maintenance (cleaning) of these latrines.…”
Section: Discussionmentioning
confidence: 99%
“…The pH results compares with those found by Farzadkia (2014) for double vault-urine diverting (DVUD) toilet which where from 6.2-13.0 due to addition of additives. Nakagiri and Niwagaba (2016) found out that, addition of lime, ash and soil resulted in corresponding pH values of 11, 9.4 and 8.8. However, they found that, pH of 11-12 is reached in treatment methods using lime.…”
Section: Urinementioning
confidence: 98%
“…However, several challenges exist in managing faecal sludge, especially in urban areas. For example, latrines may overflow due to continued use or abandoned without new latrine construction (Nakagiri et al, 2015;Blackett et al, 2014). Pathogen reduction during the management of faecal sludge is covered in the Sludge Management: Biosolids and Faecal Sludge chapter.…”
Section: Managing Outputsmentioning
confidence: 99%
“…Use of water for anal cleansing adds moisture to the pit contents, whereas dry cleaning material increases the solids accumulation rate up to 90 liters/person/year . The rate of solids accumulation can be estimated as 40-60 liters/person/year depending on the type of anal cleansing materials employed by users, although the range can be as variable as 19-90 liters/person/year (Nakagiri et al, 2015). Therefore, to allow sufficient time for filling, the pit volume should be ≥ 1,000 L .…”
Section: Pit and Slab Design And Constructionmentioning
confidence: 99%